STRATEGIES OF TEACHERS IN OVERCOMING CHALLENGES IN TEACHING ENGLISH AT THE ELEMENTARY SCHOOL LEVEL - Ahmad Royhan Lubis; Dila Amelia Putri; Syahira Azkia; Eva Betty Sianjuntak; Dea Yunita Nasution (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study explores the strategies employed by teachers to address the challenges encountered in teaching English at the elementary level. Based on interviews and literature review, several key obstacles such as low student interest, traditional teaching methods, and inadequate learning environments are identified. The findings suggest that implementing holistic, engaging, and student-centered approaches such as Project-Based Learning (PjBL), Differentiated Instruction, and innovative techniques like Total Physical Response (TPR) and Show & Tell can significantly improve learning outcomes. Additionally, the role of teachers as facilitators and motivators, fostering positive learning atmospheres, and involving parents are critical components for success. The strategies outlined aim to enhance effective learning in bilingual contexts and promote students’ personal and social skills